2021
DOI: 10.3390/agronomy11020272
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Agro-Ecological Apple Replant Disease (ARD) Management Strategies: Organic Fertilisation and Inoculation with Mycorrhizal Fungi and Bacteria

Abstract: Apple replant disease (ARD) impacts the economic yield of orchards by physiological and morphological suppression of apple trees on replanted soils. The complexity of replant disease caused by a plethora of biological interactions and physical properties of the soil requires complex management strategies to mitigate these effects. Based on expert recommendations, we selected two management strategies linked to agroecological principles of (a) organic fertilisation with a specific mulch composition (MDK) and (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Development of an integrated approach to the management of ARD has generally been lacking in terms of defining modes of action determining disease control as well as optimizing efficacy beyond the "try and see what happens" approach. A broad spectrum of soil amendments, including composts (Wilson et al, 2004;Yao et al, 2006;Van Schoor et al, 2008;Braun et al, 2010), fertilization programs (Traquiar, 1984;Wilson et al, 2004;Cavael et al, 2021) and use of green manure or cover crops (Edwards et al, 1994;Merwin, 1995;Mazzola and Mullinix, 2005;Yim et al, 2017;Kanfra et al, 2021) have been evaluated for the ability to ameliorate replant disease symptoms. In large part, these soil amendment strategies were unsuccessful in managing ARD (Wilson et al, 2004;Yao et al, 2006;Van Schoor et al, 2008) although a short-term benefit in terms of vegetative growth was, Left panel: relative quantity of myo-inositol as determined by LC-MS QTOF analysis (Leisso et al, 2017) in root exudates of micro-propagated G.935 and M.26 plantlets cultivated in root elongation medium (Yepes and Aldwinckle, 1994).…”
Section: Functionality Of Soil Amendment-rootstock Genotype Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of an integrated approach to the management of ARD has generally been lacking in terms of defining modes of action determining disease control as well as optimizing efficacy beyond the "try and see what happens" approach. A broad spectrum of soil amendments, including composts (Wilson et al, 2004;Yao et al, 2006;Van Schoor et al, 2008;Braun et al, 2010), fertilization programs (Traquiar, 1984;Wilson et al, 2004;Cavael et al, 2021) and use of green manure or cover crops (Edwards et al, 1994;Merwin, 1995;Mazzola and Mullinix, 2005;Yim et al, 2017;Kanfra et al, 2021) have been evaluated for the ability to ameliorate replant disease symptoms. In large part, these soil amendment strategies were unsuccessful in managing ARD (Wilson et al, 2004;Yao et al, 2006;Van Schoor et al, 2008) although a short-term benefit in terms of vegetative growth was, Left panel: relative quantity of myo-inositol as determined by LC-MS QTOF analysis (Leisso et al, 2017) in root exudates of micro-propagated G.935 and M.26 plantlets cultivated in root elongation medium (Yepes and Aldwinckle, 1994).…”
Section: Functionality Of Soil Amendment-rootstock Genotype Integrationmentioning
confidence: 99%
“…The tolerant rootstock G.890 consistently possessed the greatest abundance of OTUs designated as Funneliformis mosseae , a species reported to suppress apple root colonization by Pratylenchus penetrans ( Forge et al, 2001 ; Gough et al, 2020 ). Although application of mycorrhizal inoculants in controlled environment studies mitigated the growth suppressive effects of ARD ( Cavael et al, 2021 ), use of an inoculant, which commonly employs a single or few species, at the field scale is unlikely to supplant infection by the diverse mycorrhizal community resident to an orchard soil system.…”
Section: Mechanisms Of Rootstock Disease Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that replant diseases are caused by a combination of biological and abiotic factors. The abiotic factors include soil physicochemical imbalances and accumulation of allelochemicals [5][6][7][8]. The biotic factors include imbalance of soil microbial community structure caused by increasing harmful microbial such as fungi (Fusarium spp., Cylindrocarpon spp.)…”
Section: Introductionmentioning
confidence: 99%
“…ARD predominantly affects newly replanted apple trees, resulting in stunted growth, heightened susceptibility to diseases, root discoloration, root tip necrosis, diminished root biomass, and potential plant mortality during the initial growth season (Kanfra et al, 2022). Furthermore, even mature apple trees suffer from decreased yield and fruit quality when affected by ARD, with severe cases resulting in tree mortality (Mahnkopp et al, 2018;Cavael et al, 2021). ARD is instigated by the accumulation of phenolic compounds or phytotoxins in the roots affected by the disease, coupled with deleterious soil pathogens, notably fungi (Fusarium, Rhizoctonia and Cylindrocarpon) and oomycetes (Pythium and Phytophthora) (Kelderer et al, 2012;Manici et al, 2018;Wang et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%